Proceedings of the 15th International Conference on Availability, Reliability and Security 2020
DOI: 10.1145/3407023.3409314
|View full text |Cite
|
Sign up to set email alerts
|

Diderot

Abstract: In this paper, an Intrusion Detection and Prevention System (IDPS) for the Distributed Network Protocol 3 (DNP3) Supervisory Control and Data Acquisition (SCADA) systems is presented. The proposed IDPS is called DIDEROT (Dnp3 Intrusion DetEction pReventiOn sysTem) and relies on both supervised Machine Learning (ML) and unsupervised/outlier ML detection models capable of discriminating whether a DNP3 network flow is related to a particular DNP3 cyberattack or anomaly. First, the supervised ML detection model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Furthermore, two DNNs were also adopted and evaluated. The first one is called DIDEROT Autoencoder and originates from our previous work in [41]. The second one was developed during this work.…”
Section: Bdac Comparative Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, two DNNs were also adopted and evaluated. The first one is called DIDEROT Autoencoder and originates from our previous work in [41]. The second one was developed during this work.…”
Section: Bdac Comparative Methodsmentioning
confidence: 99%
“…The aforementioned cyberattacks are implemented by Smod, a widely known pen-testing tool related to Modbus [39,40]. The Modbus Network Flow-Based Anomaly Detection Model adopts the DIDEROT Autoencoder [41], identifying anomalous Modbus/TCP network flows. The DIDEROT autoencoder is analysed in our previous work in [41].…”
Section: Big Data Analysis Enginementioning
confidence: 99%
See 2 more Smart Citations
“…Attacks against the industrial sector, as indicated from past incidents, can have severe consequences. Such incidents include the December 2015 cyberattack against Ukraine's power grid, which resulted in complete electricity disruption for 225,000 people [12,13]. In addition, as Stuxnet, the first known cyber warfare weapon [14,15], indicated, nuclear power plants have also been targeted by cyberattacks, thus emphasizing the urgent need for adequate security measures in such critical domains.…”
Section: Introductionmentioning
confidence: 99%